A Modern Curriculum: Data-Driven Decision Making and AI in Accounting - Moran, Wilfredo (Universitas Negeri Malang, 2026)
This paper explores the need to re-evaluate accounting curricula and to incorporate essential data analytics and AI. In this way, it prepares students for the technological demands of the modern accounting profession and ensures that the accounting curriculum keeps up pace with the CPA Evolution Initiative. It explores the evolving landscape of accounting, the benefits of data-driven decision-making, the impact of digital transformation on accounting practices, ethical considerations, challenges and opportunities, pedagogical approaches, the benefits of Industry Partnerships and Collaborative Initiatives, and barriers to implementation. Furthermore, the paper emphasizes the importance of analytical skills and ethical awareness needed by future accountants. By integrating data analytics and AI into accounting curricula, educational institutions can effectively prepare future accountants to navigate the challenges and opportunities these technologies present, ensuring students possess the skills and knowledge to navigate the evolving landscape of the profession. The aim is to provide a roadmap for equipping future accountants with the competencies needed to thrive in the evolving world of data analytics and AI-driven finance and business. It is strongly recommended that curriculum reform be implemented and that students continue learning about data analytics and AI as they evolve. Continuous learning is essential for staying ahead of the curve.